Quantification of phenolic derivatives and antioxidant activity of the leaves of Chamaecrista diphylla (L.) Greene (Fabaceae)) - Reis, José Diogo Evangelista; Gomes, Paulo Wender Portal; Muribeca, Abraão de Jesus Barbosa; Castro, Marcela Natalia Rocha de (Scientia Plena, 2020)
Based on chemotaxonomy, the specie Chamaecrista diphylla (L.) Greene became the object of study of this work, since it is part of the same genus of C. nictitans, where there are proanthocyanidins, which act against the Herpes Simplex Virus. Thus, this work aimed to determine the compounds phenol content and antioxidant potential of extracts and fractions of leaves C. diphylla. Quantitative analysis showed ethyl acetate fraction (F-AcOEt) and ethanolic extract (EE) showed the highest levels of phenolic compounds, flavonoids and condensed tannins. Referent at antioxididant activity, the EC50 value for F-AcOEt (0.11 mg.mL-1) was better than the ascorbic acid standard (0.13 mg.mL-1), indicating a strong activity. It can also be noted that the content of flavonoids and condensed tannins are strongly correlated with antioxidant activity. Therefore, it is suggested that C. diphylla specie have secondary metabolites, flavonoids and tannins, with promising biological actions for application in the pharmaceutical and cosmetic industry.